Boundary integral formulations for noise scattered by helicopter fuselage - Poggi, C.; Bernardini, G.; Testa, C.; Gennaretti, M. (My University, 2018)
The paper deals with a theoretical-numerical comparison among integral formulations for the prediction of noise scattered by moving bodies. Three acoustic scattering integral formulations for the solution of the velocity potential wave equation are considered: a recently proposed linearized boundary-field integral formulation, and two widely applied boundary integral approaches based on Taylor and Taylor-Lorentz transformations. Aim of the work is to highlight their theoretical differences and limits of applicability, while examining their capability of capturing the influence of body motion and corresponding nonuniform mean flow around it on the scattered noise field. Numerical results concern a rigid translating sphere impinged by sound waves emitted by a co-moving pulsating point-source and a helicopter fuselage impinged by noise radiated by main- and tail-rotor.